1990
DOI: 10.1161/01.cir.81.2.638
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous conductance catheter and dimension assessment of left ventricle volume in the intact animal.

Abstract: We compared left ventricle (LV) volume (V) simultaneously measured using the conductance catheter (VM) with volume calculated from three LV dimensions (VD) determined ultrasonically from endocardial crystals. Seven adult mongrel dogs (20-30 kg) were anesthetized and instrumented to measure micromanometer LV pressure and V. Three pairs of crystals were placed orthogonally in subendocardial positions and a conductance catheter was placed in the LV retrograde across the aortic valve. Under steady-state conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
2

Year Published

1991
1991
2009
2009

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(43 citation statements)
references
References 45 publications
0
41
0
2
Order By: Relevance
“…54 There are limitations to the volume catheter method for volume assessment that should be considered. Although prior studies have shown good linear correla-tions between conductance catheter signals and other measures, [55][56][57] there are concerns about potential nonlinearity to the signal.56-" However, this limitation was unlikely to have significantly influenced the results.…”
Section: Study Limitationsmentioning
confidence: 95%
“…54 There are limitations to the volume catheter method for volume assessment that should be considered. Although prior studies have shown good linear correla-tions between conductance catheter signals and other measures, [55][56][57] there are concerns about potential nonlinearity to the signal.56-" However, this limitation was unlikely to have significantly influenced the results.…”
Section: Study Limitationsmentioning
confidence: 95%
“…LV contractility was quantified by the ESPVR, represented by the slope (Ees) of a straight line connecting the upper left-hand corners of the pressure-volume loops when loading conditions are changed by inflow occlusion (lo, 13,14) and by the volume intercept of the relation at a fixed pressure of 14 kPa (V14). We used this value to quantify its position along the volume axis as explained elsewhere ( 1 5).…”
Section: Materials a N D Methodsmentioning
confidence: 99%
“…The validity of this technique for assessment of cardiac contractility has been established previously in adult animals 25 and has been adapted for analysis of newborn cardiac function by our group. 7 Recently, Applegate et al 26 have shown that the conductance catheter accurately measures absolute volumes at steady state but can underestimate the slope and position of the end-systolic PV relation when it is determined by caval occlusion. However, the end-systolic PV relation accurately measures the direction and magnitude of change in LV systolic function.…”
Section: = 16mmmentioning
confidence: 99%